Analysing The Impact of Student Health Post COVID-19 Pandemic And Providing A Solution Using Digital Technologies - Surya Kant Pal; Amit Kumar Attri; Rita Roy; Varun Mohan; Santosh Kumar; Ajay Kumar Badhan; Manish Mohan Baral; Subhodeep Mukherjee (ACHSM, 2023)
This COVID-19 has created enormous uncertainty into important parts of national and global society, including schools and institutions. This uncertainty had halted the normal functioning of students. For example, it is unclear how the institute's shutdown last spring affected students' academic performance. Similarly, the quick transition to virtual learning in the academic years will continue to have an impact on academic performance. Despite the uncertainties, there is a growing consensus that the lockdown and school and college closures caused by COVID-19 harmfully influenced students' academics, mental health, and physical health. This research study examines how students in schools and colleges feel post lockdown. This study also highlights how the digital technologies and its applications in improving the educational process.